Dielectric Properties of Parkia Powder Agar and Its Blends with Ethyl Cellulose - Sannakki, Basavaraja; Nivrtirao, Eknath; Anita (Asian Journal of Chemistry, 2011)
The dielectric properties and A.C. conductivities of parkia powder agar for different sample thicknesses and its blends with ethyl cellulose for various weight percentages have been studied as a function of frequency over the range 50 Hz-5 MHz at room temperature. The characterizations for crystallinity of parkia powder and its blends have studied using XRD. The morphological studies have been made using the SEM. The value of dielectric constant of parkia powder agar decreases gradually as thickness of the sample decreases. But as thickness of the sample increases the dielectric constant decreases exponentially over the frequency range 50 Hz to 10 KHz and afterwards it remains constant as frequency increases. This leads to the occurrence of changes in the properties of dielectrics of parkia powder agar as thickness of the sample increases. In case of parkia powder agar blends with ethyl cellulose the dielectric constant decreases gradually up to frequency of around 1 KHz and at higher frequencies it remains constant over all weight percentages of the ethyl cellulose. It is also observed that the dielectric constant of parkia powder agar blend with ethyl cellulose decreases as weight percentage of the ethyl cellulose increases. The A.C. conductivity of parkia powder agar remains constant over the frequency range 50 Hz to 300 KHz and afterwards the conductivity increases exponentially as frequency increases. Further, it is observed that A.C. conductivity of parkia powder agar increases as thickness of the sample increases in the frequency range of 300 KHz to 5 MHz. The dielectric loss of parkia powder agar increases as thickness of the sample increases. In case of its blends with ethyl cellulose the dielectric loss decreases as the weight percentage of ethyl cellulose increases.